Paul's Knowledge of Aristophanes. (June 2017) - Griffith, R. Drew
The book of Acts plausibly claims that Paul was also named Saul. Yet in neither the genuine nor the deutero-Pauline epistles does this name appear. Several scholars have suggested that Paul avoids the name, because in Greek σαῦλος describes 'the loose, wanton gait of courtesans or Bacchantes'. This brief article argues that the word was not current in Hellenistic Greek, and that the only classical author in whom Paul might have found it is Aristophanes, whose plays were deemed by Hellenistic schoolmasters to be the most accurate reflection of Athenian speech in its golden age and hence the best possible stylistic models for imitation. I conclude that Paul was familiar with the work of Aristophanes, and that he was able to 'become all things to all people' because his own formation in Greek as well as in Jewish literature was traditional and broad.